Constitutive equations for the kinetics of swelling of hydrogels. (November 2016) - Drozdov, A.D.; Papadimitriou, A.A.; Liely, J.H.M.; Sanporean, C.-G.
Highlights: Constitutive equations are developed for the kinetics of swelling of hydrogels. The effect of constraints on transient water uptake is studied numerically. Results of simulation show good agreement with observations on NIPA, AAm, HEMA, and gelatin gels. Graphical abstract: Abstract: Governing equations are reported for the kinetics of swelling of neutral gels subjected to finite deformations. Transport of solvent through a polymer network is described by the nonlinear diffusion equation with an equivalent diffusivity strongly affected by volume fraction of the solid phase. Material constants are determined by fitting observations in water uptake tests on NIPA, AAm and gelatin gels (taken from the literature) and HEMA gels (reported in this study) under unconstrained (spherical particles) and constrained (free-standing films and thin films attached to rigid substrates) swelling. Good agreement is demonstrated between the experimental swelling diagrams and results of simulation.